Extremism Film List - Jipson, Art; Becker, Paul; Byers, Bryan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The following list of films and videos are resources that we have used in our classes on extremism, prejudice, and hate crime. These descriptions are meant to help you establish conversations with students about the nature of bias, prejudice, extremism, racism, and more. This list is only partial and is offered as suggestions for films and video with which teachers can use for their own consideration or to establish conversations in classes. It is important that any film, video, and movie that is used in class is offered as an illustration rather than a definitive expression of research, theories, and activism. These films are means to an end rather than an end in themselves; that is they demonstrate key course ideas.